2018
DOI: 10.1007/s12178-018-9498-8
|View full text |Cite
|
Sign up to set email alerts
|

Centers for Disease Control and Prevention 2017 Guidelines for Prevention of Surgical Site Infections: Review and Relevant Recommendations

Abstract: The updated guidelines include generalized recommendations for parenteral antimicrobial prophylaxis, non-parenteral antimicrobial prophylaxis, glycemic control, normothermia, oxygenation, and antiseptic prophylaxis. The arthroplasty section includes recommendations for blood transfusion, systemic immunosuppressive therapy, and antibiotics during drain use. There was low-quality evidence precluding recommendations for preoperative intra-articular corticosteroid injections, orthopedic surgical space suits, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…The immune function of these young patients with SLE was comparative to the control group. The latest CDC guideline for prevention of SSI reviewed and concluded that the effect of steroid and immunosuppressive agent on the occurrence of SSI in prosthesis joint arthroplasty was uncertain [ 22 ]. Although the use of steroid, biologic agent, and DMARDs before joint replacement arthroplasty should be carefully evaluated and adjusted based on the 2017 American College of Rheumatology/American Association of Hip and Knee Surgeons Guideline to lower the potential adverse events, such as wound healing or SSI [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immune function of these young patients with SLE was comparative to the control group. The latest CDC guideline for prevention of SSI reviewed and concluded that the effect of steroid and immunosuppressive agent on the occurrence of SSI in prosthesis joint arthroplasty was uncertain [ 22 ]. Although the use of steroid, biologic agent, and DMARDs before joint replacement arthroplasty should be carefully evaluated and adjusted based on the 2017 American College of Rheumatology/American Association of Hip and Knee Surgeons Guideline to lower the potential adverse events, such as wound healing or SSI [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 13 A total of 446 and 582 patients were eligible for inclusion before and during the intervention studies, respectively. Among these, 62 and 49 patients with SSI within 30 days after surgery based on 2017 SSI criteria were defined by the Centers for Disease Control and Prevention 16 and identified by medical staff through a healthcare personnel-based survey and a patient-based telephone survey. 13 We included SSI from superficial, deep and organ space wounds, resulting from 11 surgical procedures related to thyroid, breast, colon, appendix, limb amputation, etc.…”
Section: Methodsmentioning
confidence: 99%
“…5 6 Published evidence suggests that the associated patient and hospital costs of SSI is about two times compared with patients without SSI. 7 8 A recent systemic review of the costs of SSI in 15 LMIC and 16 European countries finds that the additional attributable SSI cost is between US$174 and US$29 610 in LMIC and US$21 and US$34 000 in Europe. 9 Potential SSI-attributable cost savings may result from an effective intervention strategy, which minimises the risk of infection and the consequent additional LOS, and extra cost of care was provided to affected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Center of disease control (CDC) estimates an additional cost of $2,734 to $26,019 to the American health care system per SSI, with an annual figure estimated between $130million and $845million (8).…”
Section: Despite Advances Have Been Made In Infection Control Practicmentioning
confidence: 99%